АВТОМАТИЗОВАНА ВИМІРЮВАЛЬНА УСТАНОВКА ДЛЯ ДОСЛІДЖЕННЯ ЕЛЕКТРИЧНИХ ХАРАКТЕРИСТИК ФОТОЕЛЕКТРИЧНИХ МОДУЛІВ - KOVAL, Vadym; OROBCHUK, Bogdan; OSADTSA, Yaroslav; KOSTYK, Liubov (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The article describes the developed and manufactured measuring device for measuring the electrical characteristics of photovoltaic modules depending on their temperature and radiation spectrum. The measuring device consists of a hardware and a software part. The basis for the hardware part is a personal computer with a built-in measuring board of a 16-bit analog-to-digital converter. The analog-to-digital converter processes signals from measuring current, voltage and temperature converters. As measuring current converters, shunts made of high-precision non-inductive resistance resistors were used. To measure a voltage greater than 5 V, dividers of the НP-9258 and НP-9251 type with conversion factors of 1:100 and 1:10, respectively, were used. The measuring device controls the load made of non-inductive active elements. In order to change the spectral composition of radiation, four light filters are used, which transmit light with wavelengths in the red, yellow, green and blue region of the spectrum. After replacing them on the radiation source, the energy of the incident radiation must be set at the level of 1000 W/m2. The software that provides the measurement process is written in the Delphi programming language and works, according to the algorithm, in automatic and manual modes. Using the measuring device the volt-ampere and volt-watt characteristics of the photovoltaic module were obtained depending on its temperature and radiation spectrum. The measuring device works in manual and automatic modes. In manual mode you can measure at least one volt-ampere characteristic, and if necessary, any number of them. In automatic mode, measurements of the current-voltage characteristics of the photovoltaic module are performed as many times as necessary to complete the transition process of heating the photovoltaic module to a certain temperature. The developed measuring device was used to study the monocrystalline photovoltaic module. The volt-ampere and volt-watt dependences of the photovoltaic module were obtained, depending on its temperature and radiation spectrum. Conclusions were made regarding the sensitivity of the photovoltaic module to the spectrum of radiation in the visible range and the decrease in energy efficiency with increasing temperature.